The production of crude palm oil in Malaysia - A., Norhidayu; Mazlan, Nur Syazwani; Radzil, R. H. M.; Amin, I. Z. M.; N., Balu (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Palm oil production contributes significantly to the Malaysian economy. Malaysia currently holds the position as the world's second-largest palm oil producer after Indonesia. This study intends to empirically test the Cobb- Douglas (C-D) production function for the palm oil production sector in Malaysia with the validity of C-D's assumptions. The significance of factors such as capital, labour and utilisation rate in the production of Crude Palm Oil (CPO) is also tested in the study. The data on the productivity of the Palm Oil (PO) mills are collected from the Malaysian Palm Oil Board (MPOB). The methods of Least Square (LS) and robustness check are carried out in the estimation of the production function. The results show a positive and significant relationship between the production of CPO and labour, capital, and the utilisation rate. This study suggests that increases in capital, labour employment and the utilisation rate will boost the production of CPO in Malaysia.